2016
DOI: 10.1175/jcli-d-16-0179.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change in the Kola Peninsula, Arctic Russia, during the Last 50 Years from Meteorological Observations

Abstract: The authors provide a detailed climatology and evaluation of recent climate change in the Kola Peninsula, Arctic Russia, a region influenced by both the North Atlantic and Arctic Oceans. The analysis is based on 50 years of monthly surface air temperature (SAT), precipitation (PPN), and sea level pressure (SLP) data from 10 meteorological stations for 1966-2015. Regional mean annual SAT is ;08C: the moderating effect of the ocean is such that coastal (inland) stations have a positive (negative) value. Examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 68 publications
1
40
0
4
Order By: Relevance
“…The most noticeable changes were observed in spring and autumn seasons and to a lesser extent in the summer. These results are consistent with studies from the circumpolar areas reporting increasing temperature trends [40,46], narrowing diurnal temperature ranges [50], shortening cold season, declining number of frost days [61][62][63][64], an increasing number of extreme warm events and a declining number of extreme cold events [11,48,51,[65][66][67][68][69]. For example, the mean temperature in Finland has risen by 0.14 • C/decade during the years 1847-2013 with the highest increases in winter and spring months [45].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The most noticeable changes were observed in spring and autumn seasons and to a lesser extent in the summer. These results are consistent with studies from the circumpolar areas reporting increasing temperature trends [40,46], narrowing diurnal temperature ranges [50], shortening cold season, declining number of frost days [61][62][63][64], an increasing number of extreme warm events and a declining number of extreme cold events [11,48,51,[65][66][67][68][69]. For example, the mean temperature in Finland has risen by 0.14 • C/decade during the years 1847-2013 with the highest increases in winter and spring months [45].…”
Section: Discussionsupporting
confidence: 90%
“…Stronger-than-average westerlies over the middle latitudes during a positive phase of NAO might, however, have a less pronounced impact on local climate in our study area than south of 65 • N [74]. Of importance are also other atmospheric oscillation patterns, such as Siberian high [46] and Scandinavian blocking [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctic Fennoscandia, which comprises northern areas of Norway, Sweden, Finland and the Kola Peninsula region of Russia, is located immediately south of the Barents Sea and has seen some marked changes in climate over recent decades (e.g., Førland et al, ; Irannezhad et al, ; Aalto et al, ; Marshall et al, ; Irannezhad et al, ; Kivinen et al, ; Swedish Meteorological and Hydrological Institute, ). Regional temperatures have increased, in particular during the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature rises of ~0.3–0.5 °C/decade between 1961 and 2010/2011 have been reported in northern Finland (Irannezhad et al, ; Aalto et al, ) while Marshall et al . () described a mean warming of ~2.3 °C from 10 stations in the Kola Peninsula from 1966–2015 (0.46 °C/decade). Seasonally, both these studies indicated that spring was the period with the greatest, statistically significant warming over the past 50 years.…”
Section: Introductionmentioning
confidence: 99%